Uma plataforma digital nos moldes da base nacional comum curricular: retorno interativo - Zagui, Greicy Nayara Pazini (2021)
The educational area has passed through deep reformulations since the creation of the National Common Curricular Base (BNCC) homologated in 2017. The BNCC aims to show a collection of fundamental and connected learnings in competences and skills. According to their definitions, it contributes in a positive way to the teacher’s work, because it conducts to the skills to be awakened in students. In line with this model, and based on this proposed new approach, the aim was to prepare an educational platform in order to provide the teacher a more consistent feedback on student learning outcomes, considering the competences and competences of the BNCC. With it, it is possible to plan procedures for the difficulties or gaps that may be presented in the process, that is, it is a technological instrument for pedagogical use based on the principles of the BNCC, through which it is possible for teachers to facilitate the interpretation of assessment results. We verified relevant information that was not previously perceived by the teacher, such as the proportion of skills worked in the classroom, more clearly planning about the assessment, individual student results and, finally, the elaboration of a student intervention plan who did not reach a certain skill.